1994
DOI: 10.1128/iai.62.9.3864-3872.1994
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and idiotypic analysis of antibodies to Cryptococcus neoformans glucuronoxylomannan

Abstract: Antibodies to the Cryptococcus neoformans capsular glucuronoxylomannan (GXM) form the basis of two potential therapeutic intervention strategies, i.e., conjugate vaccines and passive antibody therapy. To better understand the molecular basis of the antibody response, the heavy-and light-chain immunoglobulin variable region (V. and VL, respectively) sequences of seven monoclonal antibodies (MAbs) to GXM were determined. Rabbit anti-idiotypic serum was made to the previously characterized murine MAb 2H1 and used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 48 publications
2
49
0
1
Order By: Relevance
“…3). Recurrent usage of light chain Vdomains in mice is consistent with V-gene usage to capsular PS in humans and in antibody responses to many other antigens (Casadeval et al, 1994;Fish and Manser, 1987;Griffiths et al, 1984;Patera et al, 1995;Scott et al, 1989). The relative absence of somatic mutations in the light chains V-genes suggests that the antibody responses were T-independent in nature.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…3). Recurrent usage of light chain Vdomains in mice is consistent with V-gene usage to capsular PS in humans and in antibody responses to many other antigens (Casadeval et al, 1994;Fish and Manser, 1987;Griffiths et al, 1984;Patera et al, 1995;Scott et al, 1989). The relative absence of somatic mutations in the light chains V-genes suggests that the antibody responses were T-independent in nature.…”
Section: Discussionmentioning
confidence: 65%
“…A pattern of recurrence exists if the same or highly related antibody gene structures are produced to the same epitope in multiple individuals/animals (Kalinke et al, 1996;Kavaler et al, 1990;Mo et al, 1993;Solin et al, 1992). A B-cell response is termed a restricted response, which is an extreme case of recurrence, when the identical VK chain (Adderson et al, 1992;Akolkar et al, 1987;Casadeval et al, 1994;Mo et al, 1993;Patera et al, 1995;Scott et al, 1989), V H chain (Pascual et al, 1992), or both Ikematsu et al, 1998;Kaartinen et al, 1984;Liu et al, 1971) are predominantly found to encode antibodies to the same epitope of independently derived clones. All of these responses have in common an antigen with a repetitive structural organization, and/or induce a co-comittant T-cell-independent B-cell response, as they do not require mature T cells to elicit an antibody response.…”
Section: Introductionmentioning
confidence: 99%
“…Anticarbohydrate antibodies that persist for years [51,52] may be important mediators of protection. In murine cryptococcosis, protective anti-GXM MoAbs express specific heavy chain isotypes, may express a specific heavy chain idiotype, and recognize distinct GXM epitopes, whereas MoAbs that recognize the same epitope and express a different isotype are nonprotective [15,17]. Human serum, like murine serum, probably contains both protective and non-protective antibodies, and the latter could obscure the efficacy of a small subset of protective antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Murine anti-GXM antibodies elicited by infection and by GXM-tetanus toxoid (GXM-TT), a conjugate vaccine, enhance survival and reduce colony counts in C. /zeo/orOTan.$-infected mice [9,16]. Antibody idiotype and isotype specificity are important 425 determinants of protection in these models [17,18]. In the pre-AIDS era, anti-CPS antibodies were shown to be a good prognostic indicator in patients with CM [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation